2000
DOI: 10.5694/j.1326-5377.2000.tb124041.x
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic status and health in Australia

Abstract: Consistent with international evidence, the findings of Australian research show that socioeconomically disadvantaged groups experience significantly higher mortality and morbidity rates. Despite marked improvements in the health of all segments of the Australian population in recent decades, during this same period there has also been an increase in socioeconomically related mortality inequalities for some conditions. Socioeconomically disadvantaged groups are more likely to engage in health‐damaging behaviou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
69
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(72 citation statements)
references
References 37 publications
2
69
0
1
Order By: Relevance
“…First, as patterns of risky health behaviours have been found to be aggregated in both rural residents and low SES individuals,27 28 rural and low SES drivers may share the same risky behaviours, such as high alcohol consumption and failure to wear seatbelts while driving 29 30. Second, drivers of low SES may drive longer distances or use less safe cars, which is also likely to be true for rural residents 31.…”
Section: Discussionmentioning
confidence: 99%
“…First, as patterns of risky health behaviours have been found to be aggregated in both rural residents and low SES individuals,27 28 rural and low SES drivers may share the same risky behaviours, such as high alcohol consumption and failure to wear seatbelts while driving 29 30. Second, drivers of low SES may drive longer distances or use less safe cars, which is also likely to be true for rural residents 31.…”
Section: Discussionmentioning
confidence: 99%
“…Equity of access to healthcare in Australia is generally accepted to mean "equal access to equal care for equal need", while recognising that the underprivileged may require more access to more care for the same health problem [14,15]. Numerous studies have shown that those of lower socio-economic status have higher mortality and morbidity rates and their behaviour is more likely to be detrimental to their health; for example, they are more likely to have a poorer diet, be less physically active, drink alcohol to excess and smoke more cigarettes [2]. As a result we would expect them to have a greater requirement for health services.…”
Section: Discussionmentioning
confidence: 99%
“…It is unlikely to be a result of underlying disease prevalence, which in many cases is higher in the socially disadvantaged. [2]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, lower SEP individuals are more likely to consume diets high in fat, low in micronutrient density, and to have lower intakes of fruit and vegetables 7 – 10. As a result, studies repeatedly find that people of low SEP possess nutrient intakes and dietary patterns that increase risk of diet-related diseases 11 12…”
mentioning
confidence: 99%